A dual role for DNA binding by Runt in activation and repression of sloppy paired transcription. - Prazak, L.; Iwasaki, Y.; Kim, A.R.; Kozlov, K.; King, K.; Gergen, J.P. (Molecular Biology of the Cell, 2021)
This work investigates the role of DNA binding by Runt in regulating the sloppy paired 1 (slp1) gene and in particular two distinct cis-regulatory elements that mediate regulation by Runt and other pair-rule transcription factors during Drosophila segmentation. We find that a DNA-binding-defective form of Runt is ineffective at repressing both the distal (DESE) and proximal (PESE) early stripe elements of slp1 and is also compromised for DESE-dependent activation. The function of Runt-binding sites in DESE is further investigated using site-specific transgenesis and quantitative imaging techniques. When DESE is tested as an autonomous enhancer, mutagenesis of the Runt sites results in a clear loss of Runt-dependent repression but has little to no effect on Runt-dependent activation. Notably, mutagenesis of these same sites in the context of a reporter gene construct that also contains the PESE enhancer results in a significant reduction of DESE-dependent activation as well as the loss of repression observed for the autonomous mutant DESE enhancer. These results provide strong evidence that DNA binding by Runt directly contributes to the regulatory interplay of interactions between these two enhancers in the early embryo.